Local Wisdom for Character Education: A Study of Character Values in Tabot Tradition in Bengkul - Een Syaputra (Indonesian Journal of Social Science Education (IJSSE), 2019)
ABSTRACT:  TABOT ceremony is an annual event, which is done by the people of Bengkulu, particularly by the Sippai tribe, to memorize the death of Husein bin Ali bin Abi Talib, the grandson of Prophet Muhammad, in Karbala war in 61 Hijri or 681 AD. In this article, the discussion will focus on the activities of the Tabot Ritual Ceremony, especially regarding the values of character education contained in. This research used descriptive qualitative method. The data collection is done by doing a literature study, then analysed it using qualitative data analysis. Based on research that has been done, the result showed that Tabot Ritual Ceremony in Bengkulu is full of character values; symbolized from the equipment used, the philosophical foundation in each activity, and values that are reflected in the activities undertaken. From what has been found, the character values contained in Tabot Ritual Ceremonies are religious values, the spirit of struggle, love peace, brotherhood, hard work, self, love of the homeland, caring culture, and responsibility, which fits the character education proposed by the curriculum centre of Indonesia.ABSTRAK:Tradisi TABOT merupakan acara rutin yang diselenggarakan oleh masyarakat Bengkulu, khsusnya suku Sipai, untuk mengenang kematian Husein bin Ali bin Ali Thalib, cucu Nabi Muhammad dalam perang Karbala pada tahun 681 H. Dalam artikel ini, pembahasan akan berfokus pada srangkaian aktivitas dalam ritual Tabot, khususnya mengenai muatan nilai-nilai pendidikan karakter yang terkandung di dalamnya. Penelitian ini dilakukan dengan metode deskriptif kualitatif. Pengumpulan data dilakukan melalui studi literature dan dianalisis menggunakan teknik analisis data kualitatif. Berdasarkan hasil studi, ditemukan bahwa Tabot adalah tradisi yang syarat akan nilai-nilai karakter, yakni sebagaimana tercermin dari peralatan yang digunakan, tujuan dasar dari aktivitas yang dilakukan dan nilai-nilai yang tercermin dari aktivitas yang dilakukan. Adapun nilai-nilai pendidikan karakter yang trekandung dalam tradisi Tabot adalah nilai religious, semangat perjuangan, cinta damai, persaudaraan, kerja keras, mendiri, cinta tanah air, dan tanggung jawab.